Revisiting the effect of the Great Liberalization on the growth of Latin America and the Caribbean, 1980-2010 - Federico Merchán; Mauricio Mesquita Moreira (Inter-American Development Bank (IDB), 2020)
As Latin America and the Caribbeans "Great Liberalization" reaches its 30th anniversary, we revisit the trade and growth debate by updating and expanding Estevadeordal and Taylors 2013 paper. To better understand the regions heterogeneity of policies and outcomes, we extend this analysis to include a larger sample of countries, a new and more disaggregated bilateral product-level tariff dataset; a longer timespan; and a country-sector analysis. The results indicate that liberalization is likely to have made a significant contribution to the acceleration in growth observed in the postliberalization periodan extra 0.6 to 0.7 percentage points on annual per-capita growth-driven by lower tariffs on capital and intermediate goods (as suggested by Solows growth model) and by the manufacturing sector.
Keywords: F10; F13; F43; F61; F62; E65; 330; Trade liberalization; growth; Latin America; intermediate goods; capita l goods